Dropshipping Dalam Perspektif Fiqh Muamalah Kontemporer - Erwandi Tarmizi; Muhammad Maulana Hamzah (ILTIZAM Journal of Shariah Economics Research, 2021)
This research aims to analysis the dropshipping model according to Islamic jurisprudence. The research is focused in completeness of the terms and conditions of sale and purchase in dropshipping system and how its related to three economic disaster namely zhulm, riba and ghoror. The novelty from this research are dividing the object of transaction into two categories, ribawi goods and non ribawi goods and critisize the arguments that allowed dropshipping transaction. Literature study is used to define the dropshipping model, normative descriptive is used to define the contract in dropshipping according to Islamic jurispridence, content analysis is used to find the syar’i solution for dropshipping. The result shows that the origin law in dropshipping is prohibited (haram) because its contain of riba nasi’ah for ribawi goods and selling before ownership for non ribawi goods. The syar’i solutions that found for dropshipping are modification in ijab qobul, wakalah bil ujroh (the dropshipper become wakil from consumer) and ba’i salam, but the last solution is marjuuh, because the capital is not handed out at the beginning of majlis.